Accelerated dual‐contrast first‐pass perfusion MRI of the mouse heart: Development and application to diet‐induced obese mice. Issue 3 (23rd April 2014) - Naresh, Nivedita K.; Chen, Xiao; Roy, Rene J.; Antkowiak, Patrick F.; Annex, Brian H.; Epstein, Frederick H.
<x xml:space="preserve">Abstract</x> Purpose Gene‐modified mice may be used to elucidate molecular mechanisms underlying abnormal myocardial blow flow (MBF). We sought to develop a quantitative myocardial perfusion imaging technique for mice and to test the hypothesis that myocardial perfusion reserve (MPR) is reduced in a mouse model of diet‐induced obesity (DIO). Methods A dual‐contrast saturation‐recovery sequence with ky‐t undersampling and a motion‐compensated compressed sensing reconstruction algorithm was developed for first‐pass MRI on a small‐bore 7 Tesla system. Control mice were imaged at rest and with the vasodilators ATL313 and Regadenoson (n = 6 each). In addition, we imaged mice fed a high‐fat diet (HFD) for 24 weeks. Results In control mice, MBF was 5.7 ± 0.8 mL/g/min at rest and it increased to 11.8 ± 0.6 mL/g/min with ATL313 and to 10.4 ± 0.3 mL/g/min with Regadenoson. In HFD mice, we detected normal resting MBF (5.6 ± 0.4 versus 5.0 ± 0.3 on control diet), low MBF at stress (7.7 ± 0.4 versus 10.4 ± 0.3 on control diet, P < 0.05), and reduced MPR (1.4 ± 0.2 versus 2.0 ± 0.3 on control diet, P < 0.05). Conclusion Accelerated dual‐contrast first‐pass MRI with motion‐compensated compressed sensing provides spatiotemporal resolution suitable for measuring MBF in free‐breathing mice, and detected reduced MPR in DIO mice. These techniques may be used to study molecular mechanisms that underlie abnormal myocardial perfusion. Magn Reson Med 73:1237–1245, 2015. © 2014 Wiley Periodicals, Inc.